2020
DOI: 10.3390/app10061906
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Solid Oxide Fuel Cell Degradation on a Microstructural Level

Abstract: The growth of nickel (Ni) particles in the porous anode is one of the most critical issues in solid oxide fuel cells (SOFC). It reduces the density of triple-phase boundaries (TPBs) over time and increases the polarization resistance of SOFC. Most of the three-dimensional models that are used to simulate this phenomenon in detail are numerically exhausting and as such intractable for on-line applications. This work presents a two-dimensional, microstructural model of reduced complexity as a trade-off between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A lower amount of agglomeration in an composite powder is very crucial to increase the electrochemical performance of the anode by decreasing the polarization resistance in the fabricated cell. 140…”
Section: Co-precipitation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lower amount of agglomeration in an composite powder is very crucial to increase the electrochemical performance of the anode by decreasing the polarization resistance in the fabricated cell. 140…”
Section: Co-precipitation Methodsmentioning
confidence: 99%
“…The study showed that NH 4 HCO 3 produced a homogeneous powder with the smallest particle size and lowest degree of agglomeration. A lower amount of agglomeration in an composite powder is very crucial to increase the electrochemical performance of the anode by decreasing the polarization resistance in the fabricated cell 140 …”
Section: Wet Chemical Methodsmentioning
confidence: 99%